Cholecystokinin in White Sea Bream: molecular cloning, regional expression, and immunohistochemical localization in the gut after feeding and fasting - Micale V.; CAMPO, Salvatore Giuseppe; D'ASCOLA, ANGELA; GUERRERA, Maria Cristina; LEVANTI, Maria; GERMANA', Antonino; MUGLIA, Ugo (PLoS ONE, 2012)
Background: The peptide hormone cholecystokinin (CCK), secreted by the midgut, plays a key role in digestive physiology of vertebrates including teleosts, by stimulating pancreatic secretion, gut motility, and gallbladder contraction, as well as by delaying gastric emptying. Moreover, CCK is involved in the regulation of food intake and satiation. Secretion of CCK by the hindgut is controversial, and its biological activity remains to be elucidated. The present paper addresses the regional distribution of intestinal CCK in the white sea bream, Diplodus sargus, as well as the possible involvement of hindgut CCK in digestive processes. Methodology/Principal Findings: Full-lengths mRNAs encoding two CCK isoforms (CCK-1 and CCK-2) were sequenced and phylogenetically analyzed. CCK gene and protein expression levels in the different gut segments were measured 3 h and 72 h after feeding, by quantitative real-time RT-PCR and Western blot, respectively. Moreover, endocrine CCK cells were immunoistochemically detected. Fasting induced a significant decrease in CCK-2 in all intestinal segments, including the hindgut. On the other hand, no significant difference was induced by fasting on hindgut CCK-1. Conclusions/Significance: The results demonstrated two CCK isoforms in the hindgut of D.sargus, one of which (CCK-2) may be involved in the feedback control of uncompleted digestive processes. On the other hand, a functional role alternative to regulation of digestive processes may be inferred for D.sargus CCK-1, since its expression was unaffected by feeding or fasting.